Creation Hypothesis in the Anthropocene Epoch - Kaczmarczyk, Andrzej (Springer International Publishing, 2018)
This book is a discourse on creation hypothesis in light of new scientific findings made in the 20th and 21st centuries, incorporating sacred texts of different religions. It also addresses the universal phenomena of information and mathematics within this context. The discourse makes an important contribution to the ongoing conversation about creationism, intelligent design, and the problems of science vs. religion. .